Roles of Secretory Immunoglobulin A in Host-Microbiota Interactions in the Gut Ecosystem - León, E. Daniel; Francino, M. Pilar (Frontiers in Microbiology, 2022)
In the gastrointestinal tract (GIT), the immune system interacts with a variety of microorganisms, including pathogens as well as beneficial symbionts that perform important physiological functions for the host and are crucial to sustain intestinal homeostasis. In normal conditions, secretory immunoglobulin A (SIgA) is the principal antibody produced by B cells in the GIT mucosa. Polyreactivity provides certain SIgA molecules with the ability of binding different antigens in the bacterial surface, such as O-antigens and teichoic acids, while cross-species reactivity allows them to recognize and interact with different types of bacteria. These functions may be crucial in allowing SIgA to modulate the complex gut microbiota in an efficient manner. Several studies suggest that SIgA can help with the retention and proliferation of helpful members of the gut microbiota. Gut microbiota alterations in people with IgA deficiency include the lack of some species that are known to be normally coated by SIgA. Here we discuss the different ways in which SIgA behaves in relation to pathogens and beneficial bacteria of the gut microbiota and how the immune system might protect and facilitate the establishment and maintenance of certain gut symbionts.